Mechanistic Insights into Phenol Oxidation by a Copper(II) Complex of a Pyridine‐ and Amide‐Containing Copolymer in an Aqueous Medium (Eur. J. Inorg. Chem. 3/2015). Issue 3 (January 2015) - Lykourinou, Vasiliki; Ming, Li‐June
Abstract : The cover picture shows the two distinct pathways for phenol hydroxylation and oxidation by the copper complex of a copolymer in an aqueous medium, that is, a dinuclear and a mononuclear mechanism with H2 O2 and air, respectively, as the oxidation agents. Despite the random sequence and heterogeneity of this copper–copolymer complex, the rates of catalysis achieved are comparable to or better than those of many metal complexes with well‐defined structures. This copper–copolymer complex may serve as a blueprint for further design of metallopolymers with various chemical and physical properties by modification of the metal‐binding ligands and the side chains. The water splash (1/125 s) and the floating leaves in the background hint the green chemistry nature of the research. Details are discussed in the article by V. Lykourinou and L.‐J. Ming onp. 375 ff . For more on the story behind the cover research, see theCover Profile .